2014
DOI: 10.1095/biolreprod.113.113217
|View full text |Cite
|
Sign up to set email alerts
|

The Fatty Acid Beta-Oxidation Pathway Is Important for Decidualization of Endometrial Stromal Cells in Both Humans and Mice1

Abstract: Embryo implantation and development requires the endometrial stromal cells (ESCs) to undergo decidualization. This differentiation process requires glucose utilization, and blockade of the pentose phosphate pathway inhibits decidualization of ESCs both in vitro and in vivo. Glucose and fatty acids are energy substrates for many cell types, and fatty acid beta-oxidation is critical for embryo implantation. Here, we investigated whether beta-oxidation is required for decidualization of ESCs. As assessed by marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…In good agreement with this role, carnitine supply to patients with asthenozoospermia results in an increase of sperm motility. Concerning the regulation, CT2 seems to respond to progesterone stimuli (Sato et al, 2007); in line with this, CT2 is expressed at a higher level during the decidualization of the endometrium that is characterized by high progesterone levels (Sato et al, 2007;Tsai et al, 2014;Liang et al, 2018).…”
Section: General Features Of Ct2 (Slc22a16)mentioning
confidence: 57%
“…In good agreement with this role, carnitine supply to patients with asthenozoospermia results in an increase of sperm motility. Concerning the regulation, CT2 seems to respond to progesterone stimuli (Sato et al, 2007); in line with this, CT2 is expressed at a higher level during the decidualization of the endometrium that is characterized by high progesterone levels (Sato et al, 2007;Tsai et al, 2014;Liang et al, 2018).…”
Section: General Features Of Ct2 (Slc22a16)mentioning
confidence: 57%
“…Previously, we reported the down-regulation of several antioxidant enzymes and proteins involved in mitochondrial ATP production in the p53 d/d uterine tissue and suggested that Trp53 deficiency lead to mitochondrial dysfunction 7 . Specifically, the mitochondrial β-oxidation pathway is important for decidualization of endometrial stromal cells in both humans and mice 28 . The β-oxidation pathway metabolizes FA to generate energy in the form of FADH2, NADH and acetyl CoA which are important coenzymes in ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the presence of C. glacialis, along with Calanus finmarchicus, in some RNA-Seq samples influenced the gene expression patterns is difficult to discern with certainty. However, we may assume that the heterogeneity of the samples is somewhat balanced by the similarity in diapause behavior between the two species (reviewed by Baumgartner and Tarrant, 2017) and by the high conservation of the investigated lipid metabolic genes (e.g., Tsai et al, 2014). Indeed, the b-oxidation pathway is considered to be an evolutionarily well-conserved metabolic process (Schulz, 1991).…”
Section: A Crude Awakeningmentioning
confidence: 99%